2021
DOI: 10.1186/s11658-021-00266-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a sensitizes the response of glioma cells to temozolomide by modulating the P53/MDM2 feedback loop

Abstract: Recently, pivotal functions of miRNAs in regulating common tumorigenic processes and manipulating signaling pathways in brain tumors have been recognized; notably, miR‐29a is closely associated with p53 signaling, contributing to the development of glioma. However, the molecular mechanism of the interaction between miR-29a and p53 signaling is still to be revealed. Herein, a total of 30 glioma tissues and 10 non-cancerous tissues were used to investigate the expression of miR‐29a. CCK-8 assay and Transwell ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The pathway leading to the expression of miRNAs is very complex and tightly regulated by several factors at different steps [ 64 ]. Altered expression of the microRNAome in GBM has been extensively studied, although the molecular mechanisms steering specific miRNA dysregulation have been elucidated only in a few cases [ 65 , 66 , 67 ]. Numerous RBPs play a crucial role in the post-transcriptional processing of pri-miRNAs and pre-miRNAs [ 68 ]: among them, the splicing factor SRSF1 has been demonstrated to regulate the expression of several mature miRNAs by a cross-talk with the enzymes involved in the processing of their precursors, through mechanisms that have been only partially explained to date [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathway leading to the expression of miRNAs is very complex and tightly regulated by several factors at different steps [ 64 ]. Altered expression of the microRNAome in GBM has been extensively studied, although the molecular mechanisms steering specific miRNA dysregulation have been elucidated only in a few cases [ 65 , 66 , 67 ]. Numerous RBPs play a crucial role in the post-transcriptional processing of pri-miRNAs and pre-miRNAs [ 68 ]: among them, the splicing factor SRSF1 has been demonstrated to regulate the expression of several mature miRNAs by a cross-talk with the enzymes involved in the processing of their precursors, through mechanisms that have been only partially explained to date [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Chen et al. reported that miR-29a can also sensitize the response of glioma cells to TMZ through regulating the p53/MDM2 feedback loop [ 173 ]. Indeed, p53-induced expression of miR-29a can cause aberrant expression of MDM2 targeted by the corresponding miRNA, thereby affecting the activity of the p53-miR-29a-MDM2 loop [ 173 ].…”
Section: Mirnas and Gliomasmentioning
confidence: 99%
“…It increased the expression of collagens, laminin and fibronectin, all components of the ECM [ 33 ]. Regulatory loops between TP53 and miR-29 exist, as TP53 can activate miR-29 expression and miR-29 can negatively regulate MDM2 expression, resulting in increased stability of TP53 [ 34 ]. The effects of multiple miRs, long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) have been implicated in regulating the PDAC microenvironment and have recently been summarized [ 35 ].…”
Section: Interactions Between Stroma and Tp53 And Their Regulation Of...mentioning
confidence: 99%
“…This also increases the resistance to treatment with the chemotherapeutic drug temozolomide. TP53 can induce the expression of miR-29 in certain cancers [ 34 , 39 ].…”
Section: Interactions Between Stroma and Tp53 And Their Regulation Of...mentioning
confidence: 99%